Implementasi Pengembangan Kurikulum di Pondok Pesantren - Agus Prasetyo (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2018)
The aim of this study analyzed the development curriculum at Pondok Pesantren Al-Aqobah and Pondok Pesantren Tarbiyatun Nasyi'in Pacul Gowang, Jombang. The aim of this study focused on the concepts of curriculum planning studying, curriculum implementation, and curriculum evaluation. This study used descriptive qualitative approach. The source of data was the headmaster Pondok Pesantren, the curriculum staff of the Islamic Boarding School and the teacher of kitab kuning. While data collection used interview, observation, and physical data. The results showed that in concept of planning, the curriculum development at Pondok Pesantren Al-Aqobah was more emphasized on the effectiveness of students acceleration in mastering turats, while at Pondok Pesantren Nasyi'in was more emphasized on the principle of continuity (istiqomah). In implementation of curriculum, Pondok Pesantren Al Aqobah used the Amtsilati method at the first year and for the last evaluation used Authentic Assessment model, and while at Pondok Pesantren Tarbiyatun Nasyi'in learning process was conducted by Bandongan method. In Evaluation of curriculum at Pondok Pesantren Al-Aqobah was conducted directly by Kyai, because the governing structure centralized on Kyai. While at Pondok Pesantren Tarbiyatun Nasyi'in, evaluation was conducted by evaluation team consist of manager Pondok Pesantren, head of madrasah, Mufattisy, mustahhiq, and teachers. Key words: Curriculum Development, Pondok Pesantren, Implementation Curriculum